2021
DOI: 10.1038/s41467-021-21386-y
|View full text |Cite
|
Sign up to set email alerts
|

Targeting NSD2-mediated SRC-3 liquid–liquid phase separation sensitizes bortezomib treatment in multiple myeloma

Abstract: Development of chemoresistance is the main reason for failure of clinical management of multiple myeloma (MM), but the genetic and epigenetic aberrations that interact to confer such chemoresistance remains unknown. In the present study, we find that high steroid receptor coactivator-3 (SRC-3) expression is correlated with relapse/refractory and poor outcomes in MM patients treated with bortezomib (BTZ)-based regimens. Furthermore, in immortalized cell lines, high SRC-3 enhances resistance to proteasome inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 48 publications
2
54
0
Order By: Relevance
“…Herein we reveal that MDC1 acts as a scaffold for Recently, ample researches have highlighted the importance of protein condensations, such as liquid-liquid phase separation (LLPS), in physiological and pathophysiological processes 26,27 . Our previous study also reported the LLPS of SRC-3 in mediating drug resistance to PIs in MM cell 19 . The acetylation and deacetylation of IDRs regulate LLPS spatiotemporally and impact membrane-less organelle formation in vivo 28 .…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Herein we reveal that MDC1 acts as a scaffold for Recently, ample researches have highlighted the importance of protein condensations, such as liquid-liquid phase separation (LLPS), in physiological and pathophysiological processes 26,27 . Our previous study also reported the LLPS of SRC-3 in mediating drug resistance to PIs in MM cell 19 . The acetylation and deacetylation of IDRs regulate LLPS spatiotemporally and impact membrane-less organelle formation in vivo 28 .…”
Section: Discussionmentioning
confidence: 67%
“…7G). In addition, using an intra-bone growing MM model established in our laboratory 19 , which can mimic the real bone microenvironment in MM patients, we treated the mice with BTZ solely or together with Rom after 2 weeks of inoculation, and found that the Rom-BTZ combination effectively alleviated bone lesion of mice destroyed by MM cells (Fig. 7K), as evidenced by a smaller size of trabecula separation at the metaphysis and diaphysis (Fig.…”
Section: Targeting Hp1γ Stability Using Hdac Inhibitor Re-sensitizes Br MM Cells To Pi Treatment In Vivo and In Vitromentioning
confidence: 99%
See 1 more Smart Citation
“…However, the mechanism by which SRC-3 regulates the progression of these cancers has not been further elucidated. Recent study presented that overexpression of SRC-3 was correlated with poor outcome of multiple myeloma patients [ 153 ]. SRC-3 interacted with histone methyltransferase NSD2 and enhanced its liquid–liquid phase separation, thereby altered the transcriptome to compromise the sensitivity of myeloma cells to bortezomib treatment [ 153 ].…”
Section: Implication Of Src-3 In Cancermentioning
confidence: 99%
“…Based on toxicity assay, no acute or chronic toxicity of SI-2 was observed in vivo. Therefore, SI-2 is considered as a highly promising inhibitor for SRC-3 and high potential candidate for developing an anti-cancer drug [ 52 , 118 , 153 , 164 , 165 , 166 , 167 , 168 ]. Besides identifying chemicals used to block the activity of SRC-3, recent studies have also developed new methods for targeting SRC-3.…”
Section: Src-3 As Therapeutic Targetmentioning
confidence: 99%